The elucidation of the anti-inflammatory mechanism of EMO in rheumatoid arthritis through an integrative approach combining bioinformatics and experimental verification - Hui, Pusheng; Zhou, Sicong; Cao, Chunhao; Zhao, Wenting; Zeng, Li; Rong, Xiaofeng (Frontiers in Pharmacology, 2023)
Emodin (EMO) is natural derivative of the anthraquinone family. It is mainly extracted from Rheum palmatum species. Previous studies have demonstrated the superior anti-inflammatory properties of EMO, but only from a single target or pathway. To explore the anti-rheumatoid arthritis (RA) mechanism of EMO, we combined bioinformatics, network pharmacology, and experimental verification. Network pharmacological methods and mining of information from GSE data sets identified CASP1, CASP3, EGFR, EGR1, FN1, PTGS2 and ESR1 as the core target proteins of EMO action. Single-cell RNA sequencing analysis indicated that these core target proteins are likely to be involved in the action of peripheral blood mononuclear cells. The anti-inflammatory effect of EMO was further verified by TNF- induced MH7A cells, which showed that EMO could block cell differentiation and reduce IL-6 and IL-1β expression. Furthermore, sequencing of EMO-treated rat synovial fibroblasts suggested that the anti-inflammatory effect of EMO may be achieved through cytokine-cytokine receptor interactions.